Sputum mucin 1 is increased during the acute phase of chronic obstructive pulmonary disease exacerbation - Zheng, Zeguang; Qi, Yafei; Xu, Xiaoming; Jiang, Hua; Li, Zhengtu; Yang, Quan; Zhang, Chenting; Zhang, Kedong; Chen, Rongchang; Wang, Jian; Lu, Wenju (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Background: Mucin 1 (MUC1) is a membrane tethered protein on airway epithelial cells. This protein is upregulated and plays an important anti-inflammatory role during acute lung inflammation. However, the relationship between sputum MUC1 level and acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is unknown. Methods: The levels of MUC1, IL-8, and TNF-α in induced sputum from 78 COPD patients were assessed by ELISA. The association between COPD exacerbation and MUC1 fragment levels was analyzed. An acute airway inflammation mouse model was established by intranasal LPS inhalation. The expression of Muc1 in lung and the levels of Muc1, TNF-α and KC in BAL fluid from mice were determined with western blotting and ELISA, respectively. Results: Higher levels of MUC1 membrane-tethered (CT) and extracellular (EC) fragments, cytokines TNF-α and IL-8, more leucocyte and neutrophil counts were found in sputum from COPD patients in acute than in remission phase. Linear regression analysis confirmed that the level of sputum MUC1 CT fragment is positively correlated with sputum neutrophil number and patients’ age; whereas the sputum EC fragment level is correlated inversely with FEV1/FVC value and positively with patients’ age. Inhalation of lipopolysaccharide (LPS) induced acute lung inflammation in mice which exhibited increased levels of Muc1 CT fragment in lung and only Muc1 EC fragment increase in BAL fluid. Conclusions: Unlike pure bacterial induced lung inflammation, both sputum MUC1 CT and EC fragments are increased during acute exacerbation of COPD. The clinical benefits from measuring the changes of various sputum MUC1 fragments in AECOPD need to be elucidated in future studies.